RUSSIAN-CHINESE COOPERATION AND SECURITY IN ASIA PACIFIC REGION - A. V. Lukin; V. B. Kashin (Сравнительная политика, 2019)
The authors argue that Russian-Chinese rapprochement is a fundamental feature of the current changing system of international relations. The two countries are effectively enabling each other to conduct independent foreign policies often in direct opposition to the West. There is a degree of complementarity between the two sides withRussiahaving comparative advantage in the military, intelligence and diplomatic fields andChinabeing an economic superpower. The region ofCentral Asiawhich, as some Western authors have expected, could become the hotpoint of the Russian Chinese rivalry. Yet in reality it became the cradle of the two countries’ cooperation which is now affecting a wide range of international issues. Shanghai Cooperation Organization (SCO) has emerged as the main platform for Russian-Chinese cooperation inCentral Asia. AfterIndiaandPakistanjoined the SCO in 2017 it is evolving into a mechanism of Russian Chinese cooperation not only inCentral Asiabut in the Indo Pacific as a whole. The Korean peninsula is another important area of coordination betweenMoscowandBeijingin the Asia Pacific.RussiaandChinahave also been working on increasing interoperability of their military forces in the region since mid 2000s. Technically they have already done a great job for preparing ground for a military alliance. However, politically they do not appear to be ready for that yet.